Metallic Binary Copper Chalcogenides with Orthorhombic Layered Structure. Issue 1726 (15th May 2015) - Kobayashi, Kaya; Kawamoto, Shinya; Akimitsu, Jun
ABSTRACT: Chalcogenide materials have regained attention after the recent recognition of the compatibility of transition metal dichalcogenides with graphene. Additionally, there has been a recent appreciation for the rich variety of properties they support due to the anomalies in the materials' intrinsic band structure. These materials generally have layered structures and weak interlayer connection through the chalcogen layer and its van der Waals type bonding. We have synthesized orthorhombic copper telluride and measured its electrical transport properties. The results of these measurements reveal that the conduction is metallic in both the in-plane and out-of-plane directions. The range of stability of this structure is examined along with the lattice constants. The independence of the resistivity in samples to changes in excess copper indicates that the transport is essentially within the conducting planes. This result shows that the material hosts two-dimensional character likely due to its covalent interlayer bonding.